109k views
5 votes
Multiply.

(−3x+4)(2x−1)

User Toschneck
by
5.6k points

2 Answers

2 votes

Answer:

−6x²+11x−4= -x-4

Explanation:

Multiply.

(−3x+4)(2x−1)

STEPS:

-6x·2+11x-4

MULTIPLY THE NUMBERS: 6·2=12

=-12x+11x-4

ADD SIMILAR ELEMENTS: -12x+11x=-x

= -x-4

User Natsume
by
5.3k points
1 vote

Answer:


\large\boxed{(-3x+4)(2x-1)=-6x^2+11x-4}

Explanation:

Use FOIL:

(a + b)(c + d) = ac + ad + bc + bd


(-3x+4)(2x-1)=(-3x)(2x)+(-3x)(-1)+(4)(2x)+(4)(-1)\\\\=-6x^2+3x+8x-4

combine like terms


=-6x^2+(3x+8x)-4=-6x^2+11x-4

User Tahnik Mustasin
by
4.7k points